Catheter Ablation in the Treatment of Atrial Fibrillation - Hesselson, Aaron B. (International Journal of Angiology, 2020)
Catheter ablation (CA) of the pulmonary veins for atrial fibrillation (AF) is growing exponentially and is the most commonly performed electrophysiologic procedure. Initial descriptions focused on CA for paroxysmal AF, and now more recently expanded in application to persistent AF and those with comorbid heart failure. Efforts to improve success have and continue to address issues such as pulmonary vein “reconnection” following ablation through different ablative energy modalities, and the use of a “hybrid” surgical/endocardial combined approach in persistent forms of AF. Technologic advances as well are concurrently seeking to improve safety, particularly regarding the incidence of atrio-esophageal fistula in this seemingly ever-growing ablation population.
Keywords: catheter ablation; atrial fibrillation; electrophysiology; ejection fraction; paroxysmal atrial fibrillation; pulmonary vein isolation; clinical trials